Implementing a dengue vaccination programme - who, where and how? - Clapham, H; Wills, B (Oxford University Press, 2018)
The complex interaction between dengue viruses and the human immune system means that development of a safe, effective dengue vaccine was never going to be simple. The only currently licenced dengue vaccine (Dengvaxia®) does, indeed, have a complex immune profile depending on recipients’ immune status, meaning that use of this vaccine is not straightforward. This commentary reviews the recommendations for vaccine use to date, and discusses issues and opportunities related to the implementation of vaccination programmes in light of these recommendations. Future dengue vaccines may also have similar profiles, so it is vital that these issues are addressed now to ensure optimal use of vaccination in the fight against dengue globally.